Motivation for and Attitudes Towards Foreign Language Learning in the Context of Functional Multilingualism in the Family Environment - Čelofiga, Jernej; Lipavic Oštir, Alja (Revija za elementarno izobraževanje, 2024)
The article examines language attitudes, motivations for language learning, and multilingualism in families of cross-border workers (CBW) from Slovenia to Austria. It focuses on how daily travel between work in Austria and home in Slovenia influences language use and family language policy. Surveying secondary school children in northeastern Slovenia, it identifies language identities and motivations, comparing those with CBW parents to those without. The study fills a research gap on language attitudes and learning strategies among CBW children, especially regarding German. Comparative analysis with younger children and students in Slovenia and highlights the complex dynamics of language policy and adaptation in migrant families.
Keywords: functional multilingualism, language policy in the family, language attitudes, cross-border workers.